The Comparative Efficacy of Intravenous Ibuprofen 400 mg and 800 mg in Acute Mechanical Low Back Pain: A Prospective, Randomized, Double-Blind Clinical Study - İbrahim Ozlu; Nurullah İshak Işık; Mehmet Yılmaz; Miray Tümer; Alp Şener; Ahmet Burak Erdem; Erdal Tekin; Safa Dönmez (Ebelik ve Sağlık Bilimleri Dergisi, 2024)
Objective: This study aimed to compare the analgesic efficacy of intravenous (IV) ibuprofen at doses of 400 mg and 800 mg for acute mechanical low back pain. Methods: A Prospective, randomized, double-blind controlled clinical trial design was employed. Patients with moderate to severe acute low back pain were recruited from emergency departments. Ethical approval was obtained, and patients provided written consent. The study adhered to ethical guidelines and Good Clinical Practice principles. Results: Of the 144 patients, demographic characteristics were similar between groups. The 800 mg IV ibuprofen group demonstrated superior analgesic efficacy compared to the 400 mg group, with no significant adverse effects reported. Conclusion: The study concludes that the 800 mg IV dose of ibuprofen was more effective in providing analgesia control for patients with acute mechanical low back pain at all time intervals except for the 30th minute.